PROSES PENINGKATAN KETERLIBATAN KARYAWAN MELALUI GAYA KEPEMIMPINAN DAN MOTIVASI KERJA - Lianda Subekti; Margono Setiawan; Sudjanto Sudjanto (University of Merdeka Malang, 2018)
The aims of this study was to determine the process of increasing the employee engagement of the nurse children’s unit in the Balai Klinik Ibu Anak RKZ Malang. This study used a qualitative approach with phenomenology design to explain the application of the leadership model hospital of directors and motivation of nurse children’s unit in an effort to increase their engagement. Data were collected by interviewing 7 informants who are senior, intermediate and junior nursing staff. Data were analyzed using the Interactive Model of Analysis. The results showed that the application leadership model of hospital director for senior and intermediate nurses through the delegation of authority and involvement in decision-making; and for junior nurses through leading by example and description of vision and mission hospitals. Intrinsic motivation of nurses in the works are a live call and pride in their work, while extrinsic motivation is the incentive, salary, promotion, exchange office space, conducive working environment and good relationship between colleagues. The existence of unresolved conflicts between the hospital director with the senior nursing staff related to dissatisfaction in the distribution of incentives encouraging the increased desire to resign from the job and is more suited completed transactional leadership models. DOI : https://doi.org/10.26905/jbm.v5i1.2322